Lexico-Typological Reflection of English Economic Terms in The Uzbek Language (Texas Journal of Multidisciplinary Studies, 2022)
The article deals with the field of terminology in Uzbek languages, namely, creation of economic terms that actively used in economic activities their lexical and typological relations, in particular, in the process of borrowing terms.